An evaluation of the policy and practice of designing and implementing healthy apartment design standards in three Australian cities. (January 2022) - Foster, Sarah; Hooper, Paula; Duckworth, Anthony; Bolleter, Julian
Abstract: Apartment development has proliferated around the world; however concern about design quality has prompted the introduction of comprehensive apartment design policies. Effective implementation of these policies promises to improve design outcomes and create apartments conducive to good health. This study benchmarked whether design requirements linked to health and wellbeing from three Australian states, each with different levels of design governance, were being implemented. Residential apartment buildings (built 2006–2016) were sampled from Sydney, Perth and Melbourne. Data were extracted from plans and elevations to calculate the implementation of quantifiable policy-specific requirements (n = 122) for all residential apartments (n = 10, 553) and floors (n = 1094) within the buildings (n = 172). Scores were computed for design objectives (e.g., indoor and private open space, daylight, natural ventilation, acoustic privacy, visual privacy) and overall policy implementation. Sydney and Perth buildings implemented 60% and 55% of all the measured requirements, respectively, whereas Melbourne implemented 43% (p = 0.000). At the time the buildings were developed, Sydney had a comprehensive performance-based design policy and Perth had some prescriptive design standards, whereas Melbourne had discretionary design guidance only. While local contextual factors also contributed to on-ground design outcomes, the findings underscored the importance of design regulation in delivering contemporary apartment buildings that include the design features that could promote residents' health. Highlights: Apartment design regulation is increasingly introduced to improve design outcomes. 172 buildings in 3 Australian cities were evaluated against 122 'healthy' standards. Scores were calculated for the percent of policy requirements implemented. Implementation scores were 60% in Sydney, 55% in Perth and 43% in Melbourne (p = 0.000). Comprehensive regulation correlated with increased uptake of healthy design standards.